2020
DOI: 10.1111/gcb.15351
|View full text |Cite
|
Sign up to set email alerts
|

Total organic carbon concentrations in ecosystem solutions of a remote tropical montane forest respond to global environmental change

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 98 publications
(248 reference statements)
1
25
0
Order By: Relevance
“…DOM leaching from forest litter by rainwater is gradually transported and adsorbed into the deeper subsoil, which is considered an essential mechanism for the formation and stabilization of SOM in mineral soils that increase soil carbon sequestration. ,, However, this study showed that the concentration of DOC in the soil solution at 20 cm of mineral soil was not significantly higher than that at 40 cm (Figure ). This may be because of the sandy texture of the soils (Table S2) and weak adsorption of DOM in the 20–40 cm soil layer in this site.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…DOM leaching from forest litter by rainwater is gradually transported and adsorbed into the deeper subsoil, which is considered an essential mechanism for the formation and stabilization of SOM in mineral soils that increase soil carbon sequestration. ,, However, this study showed that the concentration of DOC in the soil solution at 20 cm of mineral soil was not significantly higher than that at 40 cm (Figure ). This may be because of the sandy texture of the soils (Table S2) and weak adsorption of DOM in the 20–40 cm soil layer in this site.…”
Section: Discussionmentioning
confidence: 60%
“…The balance between the production and decomposition of DOM can contribute to dynamic DOC concentration fluctuations. The former mainly involves litter, microbial biomass, root exudates, decomposition, and/or desorption of SOM, and the latter includes DOM sorption, mineralization, and leaching. , In this study, the temperature increased gradually during the rainy season, probably leading to an increased DOM input from plant sources, such as plant litter and root exudates, and more decomposition from more active microorganisms. However, a study on Canadian forests found that increased temperature increased the carbon input and the CO 2 /DOC ratio, indicating that mineralization was relatively sensitive to temperature .…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Further study of carbon and nitrogen fluxes from vegetation and streams during winter periods is warranted especially since stemflow solute fluxes are sensitive to winter meteorological event type (Levia, 2003). Wilcke et al (2020) reported a climate-related decrease in total organic carbon concentration in throughfall from 1998 to 2013 in a tropical montane forest while concentrations in stemflow increased over the same period suggesting that climate change may influence throughfall and stemflow differently. Thus, improved understanding of how throughfall, stemflow and stream solute export varies with precipitation event characteristics is critical to assessing the sensitivity of these ecologically important biogeochemical fluxes to climate forcing.…”
Section: Implications For Climate Changementioning
confidence: 99%